AB0186 ASCA (anti-saccharomyces cerevisae antibody) in scleroderma. (15th June 2017) - Fedrigo, A; Santos, TAFG dos; Bortoluzzi, A; Skare, T; Nisihara, R
Abstract : Background: The majority of Scleroderma (SSc) patients have gastrointestinal involvement. Motility is usually compromised but few studies address permeability changes in the intestinal wall. ASCA is an antibody direct against mannan in the cell wall of Saccharomyces cerevisiae, the baker's yeast that is found mainly when the small bowel is involved in Chron's disease. Nowadays ASCA is regarded more as a marker of increased gastrointestinal permeability than as a serological autoimmune marker of intestinal inflammatory disease. ASCA levels (anti-Sacharomyces Cerevisae antibodies) are associated with increased intestinal permeability. Objectives: At present we study the presence of ASCA in the serum of SSc patients aiming to know if there is increased intestinal permeability in this disease and if this is related to any clinical, demographic and treatment data. Methods: Seventy four SSc patients and 57 healthy controls were studied for ASCA (IgG and IgA) positivity by ELISA. ASCA positivity was associated with demographic, clinical, severity index (Medsger score) and serological data in SSc patients. Results: ASCA IgG levels were high in 26/74 (43.7%) patients from SSc group and 1/57 (5.2%) of controls (p<0.001); IgA ASCA was high in 12/74 (16.2%) from SSc group and 3/57 (1.7%) of controls (p=0.006). In univariated analysis IgG ASCA high levels associated positively with African background (p<0.0001) and negatively with anticentromere antibodies (p=0.013); ASCA IgA had a negative association with Medsger score (p=0.05). In multivariated analysis IgG ASCA associated independently only with African ethnic background. Conclusions: Positivity for IgG and IgA ASCA are higher among scleroderma patients than controls. African descendants have more positivity for IgG ASCA and ASCA IgA were less commonly seen in patients with more severe disease. References: Sallam H, McNearney TA, Chen JD. Systematic review: pathophysiology and management of gastrointestinal dysmotility in systemic sclerosis (scleroderma). Aliment Pharmacol Ther. 2006; 23: 691–712. Cobden I, Rothwell J, Axon ATR, Dixon MF, Lintott DJ, Rowell NR. Small intestinal structure and passive permeability in systemic sclerosis. Gut. 1980; 21:293–8. Ghoshal UC, Ghoshal U, Singh H, Tiwari S.Anti-Saccharomyces cerevisiae antibody is not useful to differentiate between Crohn's disease and intestinal tuberculosis in India. J Postgrad Med. 2007; 53:166–70. Assessment of intestinal permeability and orocecal transit time in patients with systemic sclerosis: analysis of relationships with epidemiologic and clinical parameters. Rheumatol Int. 2003; 23:226–30. Catanoso M, Lo Gullo R, Giofré MR, Pallio S, Tortora A, Lo Presti M, et al. Gastro-intestinal permeability is increased in patients with limited systemic sclerosis. Scand J Rheumatol. 2001; 30: 77–81. Disclosure of Interest: None declared